Teaching English And Communicating English Skills To Increase Domestic Tourism On The Pasir Putih Beach Of Lake Toba - Nurliani Siregar (Universitas Pahlawan Tuanku Tambusai, 2023)
In teaching Basic English for Tourism, the focus is on basic listening and speaking skills designed for English learners who need to acquire specific vocabulary from their field of work. This research involves students as research subjects in various listening, vocabulary, and speaking activities in everyday environments. This research focuses on teaching English which is in great demand in their activities such as customer service, tourism and hospitality sectors. English teaching content areas are structured from the basic foundations of English to more complex English structures. As the chapter progresses, students recycle and expand their knowledge by focusing on listening and speaking skills so students can acquire the target language.